Root and leaf abscisic acid concentration impact on gas exchange in tomato (Lycopersicon esculentum Mill) plants subjected to partial root-zone drying - Valerio, Maria; Lovelli, Stella; Sofo, Adriano; Perniola, Michele; Scopa, Antonio; Amato, Marianna (Italian Journal of Agronomy, 2017)
Partial root-zone drying (PRD) is a deficit irrigation technique with great potential for water saving. A split-root experiment was conducted on tomato in controlled environment in order to test the response of two long-time storage cultivars to PRD. Ponderosa tomato, a cultivar with yellow fruits, was compared to Giallo tondo di Auletta, a local cultivar from southern Campania (Italy). Plants were subjected to three irrigation treatments: plants receiving an amount of water equivalent to 100% of plant evapotranspiration (V100); plants in which 50% of the amount of water given to V100 was supplied (V50); and plants where one root compartment was irrigated at 50% of water requirements and the other compartment was allowed to dry, and thereafter every side was rewetted alternatively (PRD). The highest levels of leaf abscisic acid (ABA) [on average equal to 104 ng g–1 fresh weight FW)] were measured in PRD and V50, at 70 days after transplantation. Root ABA concentration in both PRD and V50 reached mean values of 149 ng g–1 FW. There were differences for the irrigation regime in root ABA biosynthesis and accumulation under partial root-zone drying and conventional deficit irrigation (V50). Assimilation rate, stomatal conductance and intercellular CO2 concentration decreased in relation to the irrigation regime by 22, 36 and 12%, respectively, in PRD, V50 and V100 at 50 days after transplantation. Ponderosa variety accumulated 20% more dry matter than Auletta and significant differences were observed in leaf area. In both PRD and V50 of the two varieties, it was possible to save on average 46% of water. Our results indicate that there is still space to optimise the PRD strategy, to further improve the cumulative physiological effects of the root-sourced signaling system.